Penerapan Model Pelatihan Berbasis SMART dalam Layanan Konsultasi untuk Kemampuan Guru BK Melaksanakan Layanan Khusus - Laia, Asa’aro; Telaumbanua, Nurhayati; Laia, Sri Wahyuni (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
The teachers complained that the training that had been going on at P4TK for a week or more, and was only filled with theories that they had previously stated, while at the end, some teachers were tired and when they returned to their assignments they only brought a sheet of research. This program aims to provide training to participants in a short time in one skill training. This training uses a SMART model approach (specific, measurable, achievable, relevant, and time-bound) with the material "Consulting Services" is a counseling service by acounselor to one or more customers (consulters) if the consultants want it, which supports the consultancy gaining insight, understanding and ways that need to be applied to deal with third party issues. This model is implemented in a face-to-face format between counselors (as consultants) and customers (as consultants). The subjects of the SMART-based training are 15 BK SMP teachers in South Nias Regency. The results show that skills are an important factor that can help improve the competence of BK teachers, who participate in consultation activities specifically for students at the school as a third party.